2014
DOI: 10.1016/j.ibmb.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the sialome of the frog biting fly, Corethrella appendiculata

Abstract: The Nematocera infraorder Culicomorpha is believed to have descended from bloodfeeding ancestors over 200 million years ago, generating bloodfeeding and non-bloodfeeding flies in two superfamilies, the Culicoidea—containing the mosquitoes, the frog-feeding midges, the Chaoboridae, and the Dixidae—and the Chironomoidea—containing the black flies, the ceratopogonids, the Chironomidae, and the Thaumaleidae. Bloodfeeding requires many adaptations, including development of a sophisticated salivary potion that disar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 76 publications
(97 reference statements)
0
32
0
Order By: Relevance
“…RNA preparation, library construction and sequencing were performed essentially as described previously (Ribeiro et al, 2014). mRNA library construction and sequencing were done by the NIH Intramural Sequencing Center.…”
Section: Methodsmentioning
confidence: 99%
“…RNA preparation, library construction and sequencing were performed essentially as described previously (Ribeiro et al, 2014). mRNA library construction and sequencing were done by the NIH Intramural Sequencing Center.…”
Section: Methodsmentioning
confidence: 99%
“…After mapping the reads to the assembled transcripts of each species transcriptome, it becomes possible to evaluate the rate of synonymous and non-synonymous polymorphism among the different protein classes. Previously we observed an increased rate of non-synonymous polymorphisms in salivary secreted proteins when compared to salivary housekeeping proteins, using transcriptomes from ticks and hematophagous insects [75][76][77][78]. Following selection of transcripts that have 100 or more read depth coverage, and with more than 15 transcripts in each functional class, it is observed that the secreted and the unknown class have the highest rate of non-synonymous to synonymous polymorphism (Additional file 1: Table S7).…”
Section: Synonymous and Non-synonymous Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…Most of the transcripts found in the present study were reported earlier in the salivary proteome of hemipterans (i.e., detoxifying and membrane associated defense transcripts, e.g., p-galactosidase, glucose dehydrogenases, chitinases; Nicholson et al 2012, Roa et al 2013), while transcripts not previously reported in this group included midnolin and sphinomyelinase. The role of midnolin-like proteins in insects is unclear, although it has been reported in the salivary glands of the frog biting fly, Corethrella appendiculata (Ribeiro et al 2014), but it is thought to be important in cellular signalling of mammalian adult tissues where it is suggested to regulate glucokinase enzyme activity in pancreatic beta cells in an attempt to regulate cellular homeostasis (Hofmeister-Brix et al 2013).…”
Section: Discussionmentioning
confidence: 99%